God of war: lore and legends ebook Lore and legends. - Barba, Rick (Dark Horse Comics, LLC., 2020)
A digital tome that authentically recreates Atreus' journal as seen in God of War, with expanded lore written in collaboration with game director Cory Barlog! The hit game is brought to life in a tangible and exciting new way as readers are invited to plumb the lore of God of War through the eyes of Kratos' son, Atreus. This digital volume chronicles Atreus and Kratos' journey through the fabled Nine Realms, from the Wildwoods of Midgard to the mountains of Jötunheim and beyond. In addition to the record of their mythic journey, this wonderous collection also includes a bestiary that was assembled during those travels, intimate dossiers of the characters that inhabit the masterfully crafted universe, and much more! Dark Horse Books and Santa Monica Studios present God of War: Lore and Legends. This lovingly produced edition is a must own item for any fan of God of War.